Carbon sequestration in an agroforestry system of coffee and Mimosa scabrella (bracatinga) in southern Brazil - Caramori, Paulo Henrique; Morais, Heverly; Leal, Alex Carneiro; Androcioli Filho, Armando; Caramori, Daniel Campos; Zaro, Geovanna Cristina; Costa, Angela Beatriz Ferreira (Agrometeoros, 2020)
Agroforestry systems (AFs) are an alternative to manage production in a sustainable manner and to adapt environments to climate change. Arabica coffee is sensitive to thermal extremes and could be one of the crops most affected by global warming. AFs can contribute to mitigate the effects of global warming through the sequestration of atmospheric carbon and its fixation in biomass and soil. This work assessed carbon sequestration and coffee yield in an AF of coffee with bracatinga (Mimosa scabrella), in a transitional climate region in southern Brazil. Two densities of bracatinga (555 and 139 trees ha-1) compared to open-grown were evaluated. Carbon sequestration was significantly higher in the AF, but coffee production was reduced by competition with M. scabrella. Further studies are needed to adjust population density and management of M. scabrella to enable the commercial use of this system.